Estado de salud oral y prevalencia de sífilis y VIH en un grupo de mujeres trabajadoras sexuales (2024)
Sex work is associated with diseases such as syphilis, gonorrhea and HIV that can cause manifestations in the oral cavity. Cross-sectional descriptive study, the sample was made up of 51 women who signed an informed consent, a medical history, periodontogram, COPD index and bacterial plaque index were completed, complementary examinations were taken and two surveys were completed in order to determine the level of knowledge in oral health and level of knowledge of STIs, using the Likert scale.